Effects of SHINBARO2 on Rat Models of Lumbar Spinal Stenosis - So Hyun Park; Ji-Young Hong; Won Kyung Kim; Joon-Shik Shin; Jinho Lee; In-Hyuk Ha; Hwa-Jin Chung; Sang Kook Lee (Hindawi Limited, 2019)
Lumbar spinal stenosis (LSS) is a major cause of chronic low back pain; however, only a few therapies which have been used in clinics still have limited effects on functional recovery. SHINBARO2 is a refined traditional formulation for inflamed lesions and relieve pain of muscular skeletal disease. This study aimed at investigating the effects of SHINBARO2 on LSS and at determining its underlying molecular mechanism in rat models. The LSS rat models were set up by surgical operations in 6-week-old male Sprague-Dawley rats. SHINBARO2 was orally or intraperitoneally administered for 14 days. The motor and sensory ability of rats were evaluated using the activity cage and hot plate method. On the termination day, total vertebrae including the disc and spinal cord were excised for ex vivo study. SHINBARO2 improved locomotor functions and pain sensitivity in LSS rat models. Mechanism study suggested that SHINBARO2 inhibited the production of nitric oxide and prostaglandin E2 in tissues from LSS-induced rats. SHINBARO2 also suppressed the expression of proinflammatory cytokines including tumor necrosis factor-α and interleukin-1β. The activation of NF-κB by LSS surgery was effectively reduced by SHINBARO2, which coincided with the inhibition of IκB degradation. In addition, brain-derived neurotrophic factor (BDNF), a potent promoter of neurite growth, and its downstream ERK signaling were also regulated by SHINBARO2. These findings suggest that the effect of SHINBARO2 might be associated in part with the anti-inflammation and pain control in LSS rat models.